REKAYASA ROUTER UNTUK PENYIMPANAN DATA - Rahmanto, Iswan Puji; Kusumaningrum, Anggraini (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2017)
Data communication is the process by which a resource on a computer can be used by other computers on the condition that the second computer is already connected to a communications network. To connect the computer to the router so the need for different data transfer network will occur. With the process of sharing data on these networks, the delivery process and data storage will be faster and cost-effective because it does not require a computer as a storage medium, but a router connected to the storage media. To facilitate the process of sharing data between the two should have an operating system to be easy in the connection process. Differences platform on the operating system being used is not a hindrance so that the computer can be connected. With samba server software and some of the settings on the computer and the router can be mutual sharing of data on the network that is connected to the router.